Cohort Life Tables from Life Courses for the Municipality of Modena: New Data and New Analyses - Nicolini, Luciano; Lopatriello, Maria Carmela (Italian Sociological Review, 2016)
The method used to construct cohort life tables starting from individual lives, which was shown to be valid in relation to small villages is also applicable to urban realities, albeit with prudence. Whenever it is necessary to select a sample, it is certainly expedient to stratify it on the basis of month of birth, after which the results may be considered reliable if the percentage of dates of death sourced is around 90%, and especially when numerous “last dates known to be alive” are available. The results also appear to be reliable in those cases in which the percentage of dates of death is lower, but it is good practice to ensure this by backing them up with those obtained by replacing the estimates based on the sample with other estimates based on data which may be sourced from the scientific literature. With more particular regard to the evolution of mortality in Modena district, it may be affirmed that this started to decline with the generations born at the end of the Nineteenth century, and therefore mainly in relation to improvements in public and private hygiene. During the Twentieth century, the industrialisation of the area appears to have had different consequences for males and females: the increase in life expectancy proved to be rather slower for the former.